Magang HR Recruitment pada PT. Mitra Adi Perkasa - Sherly Febiyanti; Annisa Kanti; Debora Debora; Dicky Supriatna (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The Merdeka Internship Program organized by the Ministry of Education, Culture, Research and Technology aims to increase students' knowledge and experience in the world of professional work. This Merdeka Internship Program is carried out at Active MAP Adiperkasa/Active MAP with HR Recruitment position. MAP Active (PT MAP Active Adiperkasa Tbk) is a retailer engaged in sports products and is a subsidiary of PT Mitra Adiperkasa Tbk (MAP). The brands managed by this company like Fitflop, Docmart, Skechers, New Balance, ALDO etc.The work done during the Merdeka Internship Program is to carry out the the end-to-end recruitment process. As for other work, such as helping project walk-in interviews which have been carried out 3 times during the internship. The Merdeka Internship Program is fully offline program so that we can learn many things directly and can be used as provisions to enter the world of work.The result of this internship program is to add new knowledge and experience that cannot be obtained from studying in college and also working professionally. In addition, hard skills and soft skills are also very well honed.